2018
DOI: 10.1017/s0022215118000932
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacies of topical antiseptic eardrops against biofilms from methicillin-resistant Staphylococcus aureus and quinolone-resistant Pseudomonas aeruginosa

Abstract: The results indicate that 4 per cent boric acid solution and vinegar with water (1:1) are potent inhibitors of biofilms from methicillin-resistant S aureus and quinolone-resistant P aeruginosa, and provide safe pH levels for avoiding ototoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The effects of BA on the number of viable microorganisms in biofilm were tested by the colony counting method. A previous study evaluated the anti-biofilm activity of BA on MRSA and P. aeruginosa resistant to quinolone, and it was stated that 4% BA suspension was a strong biofilm inhibitor (24). In the current study, it was found that BA reduced the number of viable microorganisms in biofilm significantly even for MRSA, P. aeruginosa and C. albicans.…”
Section: Discussionsupporting
confidence: 49%
“…The effects of BA on the number of viable microorganisms in biofilm were tested by the colony counting method. A previous study evaluated the anti-biofilm activity of BA on MRSA and P. aeruginosa resistant to quinolone, and it was stated that 4% BA suspension was a strong biofilm inhibitor (24). In the current study, it was found that BA reduced the number of viable microorganisms in biofilm significantly even for MRSA, P. aeruginosa and C. albicans.…”
Section: Discussionsupporting
confidence: 49%
“…A single-animal study suggested ototoxicity for acetic acid solutions with pH<5.0 (5% acetic acid has pH 2.4) (40), although the ototoxicity of acetic acid has not been systematically studied. Four percent boric acid solution has been found to inhibit PA biofilm formation (41), while reports of activity against SA biofilms are mixed (42,43); the efficacy of boric acid powder against biofilms has not been assessed. Boric acid 4% solution may be ototoxic in alcohol but not distilled water solutions (44), while there is no evidence of ototoxicity for boric acid powder in animal studies (45).…”
Section: Biofilm Dispersal Is Not the Answermentioning
confidence: 99%
“…A new insight revitalizes the findings of Hippocrates that suggest vinegar is an effective treatment of burns to avoid infection. Acetic acid is capable of treating particularly pseudomonal wound infections and can break down biofilms [16,17]. Hippocrates was also known to use red wine with similar effects to treat burn wounds [9] (p. 367 et sqq.).…”
Section: Plant-based Productsmentioning
confidence: 99%